Financing Pacific Governments for Pacific Development - Edwards, Kim (World Bank, Washington, DC, 2017)
The small Pacific Island Countries (PICs) face unique constraints which pose public financing challenges beyond those faced by other small island developing states. The PICs also face frequent natural disasters and climate-related impacts which have destructive effects on livelihoods and the capital stock. Further compounding these challenges, the process of accessing finance from development partners after a disaster can be lengthy, difficult, and uncertain, the resulting allocation of resources across projects and sectors may not be optimal, and the overall envelope of available finance is often insufficient to return the physical capital stock to its pre-disaster level. This paper provides a quantitative assessment of the outlook for government finances in the PICs over the next 25 years. Section one gives introduction. Section two assesses current public expenditure and revenue trends in the PICs and presents a range of scenarios for the evolution of government finances through to 2040. Section three examines longer-term prospects for meeting these financing needs, including via official development assistance, trust fund flows, and debt. Section four considers how the PICs’ capacity to meet their financing needs will be affected by the extent to which they take advantage of the revenue- and growth-enhancing opportunities described in the other Pacific possible background papers. Section five examines whether there is scope to improve the modalities, terms, and timing of aid delivery, including in response to natural disaster. Development assistance currently plays a key role in supporting public service delivery in the Pacific, and this role is likely to remain important over the next 25 years: working together to ensure that aid is provided as efficiently as possible is therefore of paramount importance. Due to the region’s high and increasing exposure to external shocks, the development of more effective financial risk management instruments will also be critical. This paper examines each of these areas of financial collaboration.